The Role Of Job Satisfaction, Stress Due To Workload And Self Efficacy On Employee Performance In Hospitality Industry - Ishak, Olfin; Santi Nururly; Nurdin Yusuf; Donny Dharmawan; Elizabeth (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
The purpose of this study is to examine if burnout and self-efficacy have an impact on workers' job satisfaction and performance. All employees are included in the research population. A sample of 100 participants was chosen using purposive and non-probability sampling approaches. The researcher employed a questionnaire as the primary research tool, and SPSS was utilized to perform quantitative analysis procedures for data analysis. The analysis's findings indicate that, to start, self-efficacy significantly affects work satisfaction. Secondly, job satisfaction is significantly impacted by burnout as well. Third, burnout and self-efficacy both significantly affect job satisfaction at the same time. Fourth, employee performance is significantly impacted by self-efficacy. Fifth, staff performance is significantly impacted by burnout as well. Sixth, employee performance is highly influenced by job happiness. Lastly, job satisfaction acts as a mediator between self-efficacy and burnout, which has a considerable impact on employee performance. Overall, these findings provide a comprehensive picture of the complex relationships between these factors in the context of path analysis. This research provides valuable insights for human resource management to improve employee well-being and performance.